Study on occupants awareness of fire safety system in airport building / Normalina Awang - Awang, Normalina (Faculty of Architecture, Planning and Surveying, 2009)
Fire safety system in one of the most important elements in building. Usually fire safety engineers have successfully designed and installed fire safety systems in buildings. Even though adequate systems are installed, failures still occur. In some cases, problems arise because the fire safety systems developed on the basis of misconceptions about occupants' behavior. Misconceptions happen because there is no proper data available on the level of knowledge of the occupants and they are generally lack of the knowledge on fire safety. This lack of knowledge on fire safety on the part of building occupants is a parallel to the misconceptions of fire safety engineers that have about people's reactions when facing with fire. The design of a fire safety system cannot be universal, nor can it be applied indiscriminately to all buildings of the same type or occupancy. Ideally, a fire safety system should be tailored to the characteristics of the building and its occupants. In airport building example if the occupant have a high awareness, it may avoid any problem. Beside that the management should expose the building occupant to the fire safety system.